A survey of pathological conditions of the genital tract of ewes i.pathology of ovaries and fallopian tubes - Metin Münir Kıran; Hüdaverdi Erer; M. Kemal Çiftçi; Fatih Hatipoğlu; Ahmet Semacan (Eurasian Journal of Veterinary Sciences)
In the present study the aim was to investigate the pathological conditions in the ovarium and fallopian tubes of ewes slaughtered at Konya abattoirs For this purpose, the reproductive tracts of 4370 ewes Irom different breeds were examined. During this study, in 210 cases (4.8%) ovaries and in 33 cases (0.75%) fallopian lubes showed some pathological conditions. The pathological changes in and around ovary were classified as follows; parovarian cysts (3.27%), follicular cysts (0.82%), cystic corpora lutea (0.16%), tubo-ovarian cysts (0.04%), oophoritis (0 14%), periovaritis and adhesions (0.53%), and male pseudohermaphroditismus (0,02%). Pathological changes of oviduct were hydrosalpinx(0.25%), salpingitis (0 25%), melanosis (0.07%). and me sosa I ping it i s - adhesions (0.39%).